The effect of mixtures of sun-dried tropical shrub legumes on intake and nitrogen balance by sheep - Fassler, OM; Lascano Aguilar, Carlos Eduardo (1995)
A feeding trial with sheep was carried out at the Centro Internacional de Agricultura Tropical (CIAT) in Colombia to investigate the concept of using mixtures of sun-dried tropical shrub legumes to dilute tannin levels in the diet and improve nitrogen (N) utilisation by ruminants. Intake, digestibility and N retention were measured with animals consuming: low quality grass (Brachiaria dictyoneura) alone; low quality grass supplemented with Cratylia argentea alone (49:51); and grass plus C. argentea with high tannin Flemingia macrophylla at 2 levels (53:37:10; 55:26:19). The 2 diets with F. macrophylla averaged 0.5 and 0.9% extractable condensed tannins. Intake and N retention were not significantly affected by legume supplementation, even though apparent N digestibility was higher when legumes were added. Urinary nitrogen was reduced as F. macrophylla increased in the legume mixture, suggesting less rumen ammonia losses due to protein protection by condensed tannins. However, with more F. macrophylla in the mixture, there was a reduction in dry matter and fibre digestion and an increase in faecal N and faecal N-ADF. These results suggest that, in formulating legume mixtures to supplement low quality forages, it is important to consider not only tannin levels but also the digestibility of the legumes used.